The Catholic School: Education of a Person with Disability in the Light of the Catholic Church Documents - Targamadzė, Vilija; Gervytė, Danguolė (Pedagogika, 2014)
Relevance. On one hand Catholic schools have a tradition of caring for the weakest, of paying attention to each person and to his or her needs; on the other hand, factually, they do not differ from other schools in the aspect of integrating of people with disabilities, as shown by the sources studied. Why is there a discrepancy between the paradigm of Catholic education and its realization? Authors (J. M. Barton (2000), M. E. Blackett (2001), J. Ruškus (2002), D. A. Bello (2006), T. J. Long, M. J. Schuttloffl (2006), A. Galkienė (2008), M. Scalan (2009), C. Ch. Grima-Farrell (2012), who have studied inclusive Catholic education pay more attention to the pedagogical or administrative questions raised by inclusive education than to the philosophical basis of such a choice. As a matter of fact, the analysis of Catholic education under the aspect of inclusive education is a new thing in Lithuania. The practical use of the research is the evaluation of the situation, with the identification of the weak aspects of inclusive education in Lithuania. This would allow, in the future, modeling the organization of the education of pupils with special needs on the basis of the paradigm of Catholic education. Problem question for the research: what is the situation of inclusive education in Catholic schools in Lithuania? How is it related to the conception of inclusive education expressed by the documents of the Catholic Church? The aim of the research: on the basis of empirical research find out the tendencies of inclusive education in Catholic Schools in Lithuania according to the documents of Catholic Church. The objectives of the research: 1. Make a survey of scientific literature about inclusive education in Catholic schools. 2. Analyze the vision of inclusive education contained in Church documents and the Church’s declarations about persons with a handicap, their needs and their rights. 3. Analyze the inclusive education in catholic schools according to the documents of Catholic Church. Methods of the research: 1. Survey of scientific literature and research results on inclusive education in Catholic schools. 2. Analyze documents of the Catholic Church from Vatican II on Catholic education and persons with a handicap. 3. Case study on the education of people with disabilities in Catholic schools. The analysis of the understanding of inclusive education in Catholic schools shows that: 1. It is obvious that students with disabilities should be integrated – this is understood as a norm and as a natural consequence of the Christian understanding of the value of each human person. 2. We underline the qualitative aspect of inclusive education – how it can be organized while, at the same time, maintaining the major components of Catholic education. 3. Practical research shows that, although Catholic education is favorable to inclusiveness, there are many obstacles to its qualitative realization: there is often a lack of financial and human resources, and, as a result, a gap between theory and practice. The documents of the Catholic Church show very clearly the theological grounds of inclusiveness: the person is accepted for his/her own valuable and unquestionable contribution to the community as a human person, since the definition of a Catholic school corresponds to that of a Christian community in which various persons, joined by a common aim live out the values of the Gospel and collaborate. The empirical method was applied in 17 Lithuanian Catholic schools, all of which were analyzed not as multiple cases, but as part of one case-situation of Catholic schools in Lithuania. The empirical research findings reveal that inclusiveness often means that students with disabilities are accepted in the common educational process, but without adapted conditions necessary for a full participation in this process and for personal success. As far as religious education is concerned, students with special needs are integrated in common programs, but there is practically no adaptation or personalization of pastoral work or moral education. The role of the disabled person in forming a community with other students is enhanced, but the vertical, transcendental dimension of his/her mission, which is underlined by the theological approach of the documents, is not mentioned by the schools authorities. Comparison between declarations of the Church documents on people with special needs and the information received from the schools shows a discrepancy between the aim and the reality as evaluated by school authorities, which is more functional than philosophical.